Accelerating the Performance of Micro and Small Enterprises in Surabaya City: Antecedents of Management Strengthening and Innovation Strategy - Wahyudiono Wahyudiono; Dwi Bhakti Iriantini; Kholidiah Kholidiah; Yuda Prawira (LPPM of NAROTAMA UNIVERSITY, 2026)
Objective: This study aims to examine the effect of management strengthening on innovation strategies and performance acceleration, as well as to examine the effect of innovation strategies on the performance acceleration of micro and small businesses. Design/methodology/approach: This research is categorized as quantitative research with an associative/ explanatory approach accompanied by hypothesis testing. The unit of analysis in this study is micro and small business actors with a population of 154. The sample size in this study was 78 (50.65%), with members of the sample taken from the population using purposive sampling, hereinafter referred to as respondents. Questionnaires were sent to respondents to be completed within a period of one month (September 1, 2025 - September 30, 2025). Findings: Path analysis reveals that management strengthening has a direct and significant effect on innovation strategy with standardized coefficient 0.362 (sig. 0.038) and on business performance acceleration with standardized coefficient 0.384 (sig. 0.037). Innovation strategy directly and significantly affects the acceleration of micro and small business performance with standardized coefficient 0.309 (sig. 0.041). These findings indicate that effective management strengthening, particularly in planning and implementation, not only facilitates innovation strategies responsive to environmental and digital changes but also leads to more efficient business processes and enhanced performance acceleration. Both management strengthening and innovation strategies are relevant predictors for accelerating the growth performance of micro and small businesses. Accordingly, hypotheses H1, H2, and H3 are supported because all antecedents tested show a direct, positive, and significant effect at a significance level below 0.05.